Hydroethanolic Extracts of Ficus pumila Linn. Is Protective against Gentamicin-Induced Kidney Damage in Rats - Larbie, Christopher; Siaw, Portia A; Zon, Solomon; Appiah-Kubi, Kwame (Journal of Advances in Medical and Pharmaceutical Sciences, 2020)
This article is published in Journal of Advances in Medical and Pharmaceutical Sciences and also available at 10.9734/JAMPS/2018/41291